Treatment of Central Nervous System Relapse in Acute Promyelocytic Leukemia by Venetoclax: A Case Report - Zhang, Xuzhao; Chen, Jinliang; Wang, Weiqin; Li, Xian; Tan, Yanbin; Zhang, Xiaohong; Qian, Wenbin (Frontiers in Oncology, 2021)
Extramedullary relapse of acute promyelocytic leukemia is a rare phenomenon and is associated with a poor prognosis, with the central nervous system being the most common site of relapse. The current treatments are still limited. Venetoclax, a selective inhibitor of BCL2, is a small molecule that can cross the blood-brain barrier and shows a potential efficacy in the treatment of chronic lymphocytic leukemia with central nervous system involvement. Although venetoclax has also been used in the treatment of acute myeloid leukemia in recent years, there are no reports of its use in the treatment of central nervous system relapse in acute promyelocytic leukemia. Here, we report a case of central nervous system relapse in acute promyelocytic leukemia that achieved complete remission after oral treatment with venetoclax. The presence of venetoclax in the patient's CSF was confirmed by testing CSF and plasma by mass spectrometry. The concentration of venetoclax in CSF was approximately 1/300 of that in plasma trough concentration. The treatment experience in this case demonstrates the potential ability of venetoclax to treat of central nervous system relapse/involvement in acute promyelocytic leukemia, thus providing a new treatment option for this kind of patient.